2018
DOI: 10.1016/j.worlddev.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Productive effects of public works programs: What do we know? What should we know?

Abstract: Public works programs (PWPs) are popular development interventions due to their potential 'double dividend' of transferring income to the poor while at the same time creating public infrastructure. However, PWPs are costly and demanding from an administrative perspective and it is not clear whether they are the most cost-effective intervention to reduce poverty. Therefore, an assessment of PW programs needs to understand which benefits and costs these programs entail relative to other interventions, and whethe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 45 publications
0
40
1
2
Order By: Relevance
“…Although CfW and PWP increased labor force participation in two cases (Liberia and Tanzania), a third study found no impacts (Ethiopia) pointing towards the need for broader evidence on these programming typologies. While this is not surprising, as global reviews have pointed out, there is a need to measure outcomes of these programs more broadly to ensure that the benefits of the work outweigh the costs (Gehrke and Hartwig 2018). Qualitative work can shed additional light on gender dynamics in economic standing and on how transitions in and out of income-generating activities may lead to more or less preferred work outlets for women that both provide economic support, sufficient leisure time, and also mitigate risk against violence and harassment, protect from other hazards and allow flexible hours for childcare.…”
Section: B Economic Standing and Productivitymentioning
confidence: 99%
“…Although CfW and PWP increased labor force participation in two cases (Liberia and Tanzania), a third study found no impacts (Ethiopia) pointing towards the need for broader evidence on these programming typologies. While this is not surprising, as global reviews have pointed out, there is a need to measure outcomes of these programs more broadly to ensure that the benefits of the work outweigh the costs (Gehrke and Hartwig 2018). Qualitative work can shed additional light on gender dynamics in economic standing and on how transitions in and out of income-generating activities may lead to more or less preferred work outlets for women that both provide economic support, sufficient leisure time, and also mitigate risk against violence and harassment, protect from other hazards and allow flexible hours for childcare.…”
Section: B Economic Standing and Productivitymentioning
confidence: 99%
“…For these individuals, the relevant “benefit” is not the overall wage received from the program but rather the difference between the program wage and the self‐employment wage. This finding has important implications for benefit‐cost analysis of the program, of which previous attempts have been somewhat pessimistic (Murgai, Ravallion, and van de Walle 2015; Gehrke and Hartwig 2018). However, the fact that NREGS also appears to offer households an alternative risk‐management strategy means that a simple comparison of monetary returns is not the relevant comparison these households make.…”
Section: Resultsmentioning
confidence: 87%
“…In this sense, it may be difficult to form a complete picture of these effects with respect to NREGS, as most studies—including this one—necessarily examine relatively short‐term impacts using quasi‐experimental methods. Nonetheless, even after accounting for these indirect benefits, it may very well be the case that alternative government policies—basic‐income schemes, for example—still dominate public works programs in certain contexts (Murgai, Ravallion, and van de Walle 2015; Gehrke and Hartwig 2018). In this regard, it is clear that NREGS is displacing some alternative forms of employment and that the opportunity cost of participation in NREGS is not zero.…”
mentioning
confidence: 99%
“…The public works programs became popular development interventions due to their potential 'double dividend' of transferring wages to the poor while at the same time creating the public infrastructure (Gehrke, & Hartwig, 2018). Public works with locally evolved norms linked with natural resource management like in MGNREGA will the yield third dividend in the form of nourishing the natural resources.…”
Section: Mgnrega As a Successful Social Safety Net And Its Spillover mentioning
confidence: 99%